Combustion synthesis of ZnSe with strong red emission. (5th May 2016) - Liu, Guanghua; Yuan, Xuanyi; Li, Jiangtao; Chen, Kexin; Li, Yuyang; Li, Laifeng
Abstract: A fast and furnace-free way is reported to synthesize ZnSe from self-sustained combustion reaction between Zn and Se. The synthesized ZnSe shows a zincblende structure and large particle size of > 100 μm, which can be reduced by two magnitude to 1.4 μm by using NaCl as diluent. It is proposed that the added NaCl can lower the reaction temperature and diminish the interfacial area of ZnSe grains by a steric hindrance effect. The ZnSe samples show the characteristic band-edge absorption in visible region, and the band gap energy is estimated to be 2.43–2.58 eV. Under an ultraviolet excitation, the ZnSe samples do not show the near-band-edge blue emission but exhibit strong red emission, which is likely related to the intrinsic point defects in ZnSe. Compared with previous studies, the ZnSe samples synthesized in this work show red emission peaks at even larger wavelength up to 730 nm. Graphical abstract: Highlights: ZnSe powders are synthesized by a fast and furnace-free way of combustion synthesis. The particle size of ZnSe can be controlled in a wide range from below 1 μm to larger than 100 μm. The band gap energy of ZnSe varies in the range of 2.43–2.58 eV. The ZnSe samples show strong red emission with a peak wavelength of 730 nm that is clearly larger than previous studies.